2010
DOI: 10.1007/s00429-010-0280-y
|View full text |Cite
|
Sign up to set email alerts
|

Cortico-basal ganglia circuitry: a review of key research and implications for functional connectivity studies of mood and anxiety disorders

Abstract: There is considerable evidence that dysfunction of the cortico-basal ganglia circuits may be associated with several mood and anxiety disorders. However, it is unclear whether circuit abnormalities contribute directly either to the neurobiology of these conditions or to the manifestation of symptoms. Understanding the role of these pathways in psychiatric illness has been limited by an incomplete characterization of normal function. In recent years, studies using animal models and human functional imaging have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
92
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(98 citation statements)
references
References 355 publications
(385 reference statements)
6
92
0
Order By: Relevance
“…This is consistent with previous reports from nuclear imaging (van der Wee et al, 2008). Enhanced connectivity in pre-motor regions suggests that SAD patients are in a state of "motor readiness", either due to abnormal input to the striatum (from amygdala or mid-brain dopaminergic neurons) as proposed as a testable model for anxiety disorders by (Marchand, 2010). Enhanced functional connectivity with striatum and regions of the OFC with SAD is equally interesting because of recent reports from task-based fMRI, highlighting the role of OFC in neural habituation in SAD (Sladky et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with previous reports from nuclear imaging (van der Wee et al, 2008). Enhanced connectivity in pre-motor regions suggests that SAD patients are in a state of "motor readiness", either due to abnormal input to the striatum (from amygdala or mid-brain dopaminergic neurons) as proposed as a testable model for anxiety disorders by (Marchand, 2010). Enhanced functional connectivity with striatum and regions of the OFC with SAD is equally interesting because of recent reports from task-based fMRI, highlighting the role of OFC in neural habituation in SAD (Sladky et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…53 Our results may provide direct evidence of the abnormal association between very basic limbic structures governing internal homeostasis (i.e., hypothalamus and amygdala) and the ventral frontostriatal system related to motivation, reward and satiety. 50,[54][55][56] In other words, the results may suggest how nonsatiated basic drives ultimately favour the generation of obsessions via a deficient inhibition of ventral frontal cortex activity. Reduced ventral frontal inhibition from the hypothalamus is consistent with both its increased response when viewing pictures of food 24,25,57,58 and its delayed or reduced satiety responses to oral nutrients, 20,21 as reported in prior imaging studies of patients with Prader Willi syndrome.…”
Section: Discussionmentioning
confidence: 94%
“…Several subcortical connections within the frontosubcortical loops are inhibitory, including striatum-globus pallidus and globus pallidusthalamus projections. 50 Accordingly, functional connectivity alterations in such pathways could express response disinhibition or facilitation. Because resting fMRI signal in all these structures is strongly, positively correlated (i.e., synchronized activity), it could be argued that subcortical connectivity in these maps better expresses fluctuations of general tonic arousal in the subcortical nuclei, rather than strictly local nucleus to nucleus influences.…”
Section: Discussionmentioning
confidence: 99%
“…& D 'Esposito, 2008;Marchand, 2010;Phan, Wager, Taylor, & Liberzon, 2002;Reiman et al, 1997). Functional connectivity analyses examining the PFC-amygdala-brainstem circuit revealed that during baseline, the vmPFC, OFC, and dlPFC time courses predicted subsequent BOLD responses in the amygdala.…”
Section: Discussionmentioning
confidence: 99%